A mix design method for alkali-activated ultra-high performance concrete with composite cementitious system
By adopting the alkali-excited ultra-high performance concrete ratio design method of composite gelling system, problems such as long proportion formation cycle and lack of theoretical guidance in the existing technology are solved, and the effect of simplifying the design process, improving universality and efficiency is achieved. .
Patent Information
- Application Number
- CN202410350923.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-26
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-03-26
AI Technical Summary
The existing alkali-excited ultra-high performance concrete mix design methods have problems such as long proportion formation cycle, lack of theoretical guidance, cumbersome and complex proportion design process, and narrow scope of application.
The composite gelling system alkali-activated ultra-high performance concrete ratio design method is adopted. By determining the compressive strength and fluidity to be matched, fly ash substitution rate, water glass solution design modulus, alkali bond ratio and water bond ratio are selected. Determine the total amount of gelling material and the amount of each component, determine the aggregate ratio based on the theory of closest particle packing, and calculate the volume content of steel fibers based on the target compressive strength.
This method simplifies the proportional design process, improves the universality and efficiency of the design, is suitable for alkali-excited ultra-high performance concrete with compressive strength between 100MPa-200MPa, expands the scope of use of the target strength method, and provides flow Sex prediction method.
Smart Images

Figure CN118609714B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a concrete mix ratio design method, in particular to a composite gelling system alkali-activated ultra-high performance concrete mix ratio design method, and belongs to the field of construction. Background Art
[0002] Ultra-high performance concrete (UHPC) has been widely used in bridges, hydraulic structures, nuclear power structures, offshore platforms and other fields due to its ultra-high strength, ultra-high toughness and excellent durability. It has also been proven to be a new type of building material with broad application prospects in the field of structural protection. Usually, the amount of cement used in UHPC is 2-3 times that of ordinary concrete (NC), and because UHPC uses a very low water-cement ratio (less than 0.25) during the preparation process, a large number of cement particles are only used as fillers and do not participate in the hydration reaction, so that the production process of UHPC consumes a lot of cement and produces a lot of CO2.
[0003] Alkali-activated ultra-high performance concrete (AA-UHPC) is a new type of ultra-high performance concrete produced with alkali-activated cement as a cementitious material. Alkali-activated cement mainly uses one or more industrial solid wastes with aluminosilicate properties (such as slag, fly ash, silica fume, steel slag, etc.) as precursors, and is a cementitious material obtained by activating the activity of the precursors with alkaline metal salts. Compared with UHPC, the preparation of AA-UHPC greatly reduces CO2 emissions and production prices and realizes the effective utilization of industrial solid wastes because alkali-activated cement is used to replace traditional Portland cement. When the concrete strength is the same, the comprehensive performance of AA-UHPC materials is better, that is, AA-UHPC shows the characteristics of better material performance, more economical and more environmentally friendly, which makes AA-UHPC have broad application prospects. However, the preparation method of AA-UHPC is more complicated than that of UHPC. Establishing a universal mix design method is the basis for promoting the application of AA-UHPC.
[0004] At present, there are three main methods for the mix design of AA-UHPC: empirical method, mathematical model method and target strength method. The empirical method relies on experience and adjusts the mix ratio of concrete after multiple trials in the laboratory to achieve the target performance. This method has no theoretical support, a long trial period, consumes a lot of manpower and material resources, and the mix ratio is not universal, so it cannot be promoted and applied; the mathematical model method is based on the theory of the most densely packed particles. This method only adjusts the proportion of each powder component to achieve the dense packing of each material component, thereby obtaining ultra-high performance concrete, but this method cannot predict the strength of concrete, nor does it consider the influence of steel fiber on the packing density of powder particles, which has certain limitations. The target strength method is a method of mix design based on the target strength as the design index and the Ca / (Si+Al) ratio and Si / Al ratio in alkali-activated concrete as the link. This method is only applicable to the case where Si / Al=2.4 and 3.8 and Ca / (Si+Al)=0.46, and has a narrow scope of application.
[0005] Among them, the empirical method mainly determines the amount of adhesive, aggregate, activator, water and fiber of AA-UHPC based on experience, and then continuously adjusts the amount of each component through laboratory trial mixing until the newly mixed and hardened AA-UHPC meets the requirements. The shortcomings are: the laboratory trial mixing method determines the amount of adhesive, aggregate, activator, water and fiber based on experience, has no theoretical basis, and the resulting ratio is not universal; secondly, the laboratory trial mixing method often requires multiple trials to obtain AA-UHPC that meets the requirements. A mature ratio scheme often takes a long period of time, a large amount of testing, and consumes manpower and material resources.
[0006] The mathematical model method is based on the theory of the most densely packed particles. The basic theory is shown in formula (1):
[0007]
[0008] Among them, U(D p )——Particle size is smaller than D p Volume fraction
[0009] D p ——Particle size
[0010] ——Minimum particle size in the system
[0011] ——The maximum particle size in the system
[0012] n——distribution modulus (0.2-0.5)
[0013] In order to minimize the packing density of the system, it is necessary to minimize the error between the target value and the fitted value, that is, to satisfy formula (2):
[0014]
[0015] When solving equation (2), it is also necessary to satisfy the constraints (3)-(5)
[0016]
[0017]
[0018]
[0019] This method mainly uses the theory of closest packing of particles to transform the proportion problem of each powder component of concrete into several known distribution functions, and then optimizes the objective function through fitting these functions. When the fitting function U(Dm) coincides or is close to the objective function U(Dt), the proportion of each function is the proportion of each component, that is, the mix ratio.
[0020] The shortcomings of the mathematical model proportioning method are: based on the mathematical model method, the most compact packing of system particles can be achieved and ultra-high concrete strength can be obtained, but this method cannot predict the strength of concrete and does not consider the influence of activators on concrete performance; in addition, the model does not consider the influence of fibers on particle packing density.
[0021] The target strength method uses the target strength as the design index of concrete. The specific steps are as follows: determine the target strength, select the molar number of sodium hydroxide, the modulus of sodium silicate and sodium hydroxide, the curing time and the curing temperature; select the water-binder ratio (W / B) and the alkali-binder ratio ((Na2O / B)%); select the Si / Al ratio and calculate the Ca / (Si+Al) ratio and calculate the mass of each component according to the element content of the raw materials (based on the cement dosage for preparing UHPC, take the total amount of adhesive, generally 800-1100kg / m 3 ), and calculate the amount of activator according to the alkali-binder ratio; determine the amount of aggregate according to the absolute mass or absolute volume method and adjust it; select the fiber type and amount according to the compressive strength; evaluate the performance, and end if it meets the requirements; if it does not meet the requirements, return to the first step. Disadvantages of mix design based on the target strength method: The target strength method mainly uses the target strength as the design indicator, and does not consider the influence of working performance; in addition, the target performance method is only applicable to the cases where the Si / Al ratio is 2.4 and 3.8, and the application range is narrow.
[0022] In summary, the existing alkali-activated ultra-high performance concrete mix design method has the problems of long mix formation cycle, lack of theoretical guidance, cumbersome and complex mix design process, and narrow scope of application. Summary of the invention
[0023] The purpose of the present invention is to solve the problems of the existing alkali-activated ultra-high performance concrete mix design method, such as long mix formation cycle, lack of theoretical guidance, cumbersome and complicated mix design process, and narrow application scope. Furthermore, a composite cementitious system alkali-activated ultra-high performance concrete mix design method is provided.
[0024] The technical solution of the present invention is: a method for designing the mix ratio of composite gelling system alkali-activated ultra-high performance concrete, which comprises the following steps:
[0025] Step 1: Determine the compressive strength and fluidity of the alkali-activated ultra-high performance concrete to be prepared;
[0026] Step 2: Determine the compressive strength and fluidity of plain concrete, as well as the curing system;
[0027] Step 3: Select the fly ash replacement rate FA / B, the water glass solution design modulus Ms (Ms = n(SiO2) / n(Na2O)), the alkali-binder ratio N / B and the water-binder ratio W / B; where n is the amount of substance, and the unit of n is mol;
[0028] Step 4: Determine the total amount of cementitious material M 胶总 ;
[0029] Step 5: Determine the amount of each component of the cementitious material;
[0030] Select the fly ash replacement rate FA / B and the silica fume replacement rate SF / B as 5% as fixed values. According to FA / B+SF / B+GBFS / B=1, determine the amount of mineral powder, fly ash and silica fume, that is, M 矿粉 、M 粉煤灰 、M 硅灰 ;
[0031] Determine the amount of activator water M according to the water-binder ratio W / B 水 ;M 水 =M 总 ×W / B
[0032] Step 6: Determine the amount of water glass solution and the amount of sodium hydroxide according to the alkali-glue ratio N / B, the designed water glass modulus Ms and the initial water glass modulus Mo, that is, M 氢氧化钠 、M 水玻璃 ;
[0033] Step 7: Determine the amount of additional tap water to be added;
[0034] According to the water-binder ratio W / B and the water content in the water glass solution, determine the amount of additional tap water M to be added. 自来水 ; is the mass fraction of water in the water glass solution;
[0035] Step 8: Determine the amount of aggregate;
[0036] According to the closest packing theory of particles, the ratio of 26-40 mesh, 40-70 mesh, and 70-110 mesh aggregates is determined as 26-40∶40-70∶70-110=x∶y∶z(α=0.23), where α is the distribution modulus. When α≥0.5, the concrete contains more coarse aggregates; when 0.2<α<0.5, the concrete contains more fine aggregates, and the particles of each component in the alkali-activated ultra-high performance concrete are smaller, so α=0.23;
[0037] Step 9: According to the sand-binder ratio and 26-40 mesh: 40-70 mesh: 70-110 mesh = x: y: z, determine the amount of three types of quartz sand: 26-40 mesh, 40-70 mesh, and 70-110 mesh, wherein the sand-binder ratio S / B = 1.0, which is a fixed value;
[0038] Step 10: Calculate the volume content and mass M of steel fiber according to the target compressive strength 钢纤维 ;
[0039] f c (X1, X2, X3, X4, 2 -110.81X2 2 -68.82X1X2)·(-0.79+9.24X3+18.88X4-17.62X3 2 -138.96X4 2 )·(1+0.17X5)
[0040] M 钢纤维 =7850kg / m3*X5;
[0041] Among them, X1 is the water glass modulus, X2 is the fly ash replacement rate, X3 is the water-binder ratio, X4 is the alkali-binder ratio, X5 is the steel fiber content, 5% is the silica fume replacement rate SF / B, 1.0 is the sand-binder ratio S / B, f c is the target compressive strength of concrete after incorporation of steel fibers;
[0042] Step 11: Conduct trial mix and evaluate whether the material properties of concrete meet the requirements. If so, end the mix design; if not, return to step 3 to adjust the mix parameters and the amount of each component.
[0043] Furthermore, before determining the compressive strength and fluidity of the alkali-activated ultra-high performance concrete, the alkali-activated ultra-high performance concrete material is first determined. The alkali-activated ultra-high performance concrete material consists of S95 mineral powder, Class F fly ash, silica fume, 26-40 mesh quartz sand, 40-70 mesh quartz sand, 70-110 mesh quartz sand, short straight steel fiber, flaky sodium hydroxide, water glass solution and water.
[0044] Furthermore, the curing system in step 2 is 90° steam curing for 48 hours.
[0045] Furthermore, step 2 also includes a stirring system, including the following steps:
[0046] Step 1: Mix the mineral powder, fly ash and silica fume determined in step 5 and stir for 2 minutes;
[0047] Step 2: Add the quartz sand determined in step 9 and stir for 1 minute;
[0048] Step 3: Add the activator determined in step 6 and stir for 4 minutes;
[0049] Step 4: Add the steel fiber determined in step 10 and stir for 2-3 minutes. The test method is: compressive strength test with 40×40×40mm 3 Cubic test block, test block loading system is 2.4kN / s±0.2kN / s.
[0050] Preferably, the short straight steel fiber has a diameter of 0.2 mm and a length of 13 mm.
[0051] Furthermore, the total amount of cementitious material in step 4 is M 胶总 =800-1100kg / m 3 .
[0052] Further, in step 52, M 矿粉 、M 粉煤灰 、M 硅灰 The calculation formula is:
[0053] M 硅灰 =M 胶总 ×SF / B;
[0054] M 粉煤灰 =M 胶总 ×FA / B;
[0055] M 矿粉 =M 胶总 ×1-SF / B-FA / B.
[0056] Furthermore, in step six
[0057]
[0058] Furthermore, the compressive strength of the alkali-activated ultra-high performance concrete to be prepared in step 1 is 100MPa-200MPa.
[0059] Compared with the prior art, the present invention has the following effects:
[0060] 1. The present invention is applicable to the mix design of alkali-activated ultra-high performance concrete with a compressive strength between 100MPa and 200MPa. This method overcomes the shortcomings of the empirical method, which has a long cycle and consumes a lot of manpower and material resources, and makes up for the shortcomings of the mathematical model method that cannot predict the target performance and cannot consider the influence of the activator. It also expands the scope of use of the target strength method and provides a fluidity prediction method. It has good universality and lays a foundation for the promotion and application of alkali-activated ultra-high performance concrete.
[0061] 2. The present invention presets the requirements for the mix ratio, and then determines the weight of each component of the concrete based on the compressive strength and fluidity of the plain concrete without the addition of steel fiber, and finally adds the steel fiber to finally achieve the set requirements for the compressive strength and fluidity of the concrete. The entire mix ratio design method has a simple, clear process and is easy to operate.
[0062] 3. The process of the proportioning method of the present invention is not only applicable to the proportioning design of the alkali-activated ultra-high performance concrete of the ternary cementitious system of mineral powder-fly ash-silica fume, but also applicable to concrete of other alkali-activated cementitious systems. In addition, the process of the method is not only applicable to alkali-activated ultra-high performance concrete, but also to other types of alkali-activated fiber reinforced concrete and alkali-activated element concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 It is a flow chart of the proportion design of the present invention;
[0064] Figure 2 It is the effect of water glass design modulus (Ms) and fly ash replacement ratio (FA / B) on expansion in plain concrete, and is used as a reference for data selection;
[0065] Figure 3 It is the effect of water-binder ratio (W / B) and alkali-binder ratio (N / B) on expansion in plain concrete, and is used as a reference for data selection.
[0066] Figure 4 It is the effect of water glass design modulus (Ms) and fly ash replacement ratio (FA / B) on compressive strength in plain concrete, and is used as a reference for data selection;
[0067] Figure 5 It indicates the effect of water-binder ratio (W / B) and alkali-binder ratio (N / B) on compressive strength in plain concrete and is used as a reference for data selection.
[0068] Figure 6 yes Figure 3 The test data diagram shows the influence of water-binder ratio (W / B) and alkali-binder ratio (N / B) on expansion; where Ms = 1.5; FA / B = 20%; SF / B = 5%; S / B = 1.0; Vstf = 0%;
[0069] Figure 7 yes Figure 2 The test data diagram shows the influence of fly ash replacement rate (FA / B) and water glass design modulus (Ms) on expansion, where W / B = 0.32; N / B = 7%; SF / B = 5%; S / B = 1.0; Vstf = 0%;
[0070] Figure 8 This is a test data chart showing the effect of steel fiber volume on expansion;
[0071] Among them, Ms=1.5; FA / B=20%; W / B=0.32; N / B=7%; SF / B=5%; S / B=1.0;
[0072] Fig. 9 It is a reference chart for selecting the composition ratio of quartz sand; it is the proportion fitting result of quartz sand determined based on the theory of the most compact particle packing;
[0073] Fig.10 It represents the fitting results of the effects of water glass design modulus (Ms) and fly ash replacement ratio (FA / B) on compressive strength;
[0074] Fig.11 The projection of fitting results showing the effect of water glass design modulus (Ms) and fly ash replacement ratio (FA / B) on compressive strength;
[0075] Fig.12 It represents the fitting residual of the effect of water glass design modulus (Ms) and fly ash replacement ratio (FA / B) on compressive strength;
[0076] Fig.13 It represents the fitting results of the influence coefficients of water-binder ratio (W / B) and alkali-binder ratio (N / B) on compressive strength;
[0077] Fig.14 It indicates the influence coefficient of water-binder ratio (W / B) and alkali-binder ratio (N / B) on compressive strength;
[0078] Fig.15 It represents the residual error of the fitting of the coefficient of influence of water-binder ratio (W / B) and alkali-binder ratio (N / B) on compressive strength;
[0079] Fig.16 It represents the fitting result of the coefficient of influence of steel fiber volume on compressive strength;
[0080] Fig.17 Represents the fitting residual of the coefficient of influence of steel fiber volume on compressive strength. DETAILED DESCRIPTION
[0081] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0082] Specific implementation method 1: Combination Figures 1 to 9 To illustrate this embodiment, the embodiment includes the following steps:
[0083] Step 1: Determine the compressive strength and fluidity of the alkali-activated ultra-high performance concrete to be prepared;
[0084] Step 2: Determine the compressive strength and fluidity of plain concrete, as well as the curing system;
[0085] Step 3: Select the fly ash replacement rate FA / B, the water glass solution design modulus Ms (Ms = n(SiO2) / n(Na2O)), the alkali-binder ratio N / B and the water-binder ratio W / B; where n is the amount of substance, and the unit of n is mol;
[0086] Step 4: Determine the total amount of cementitious material M 总 ;
[0087] Step 5: Determine the amount of each component of the cementitious material;
[0088] Select the fly ash replacement rate FA / B and the silica fume replacement rate SF / B as 5% as fixed values. According to FA / B+SF / B+GBFS / B=1, determine the amount of mineral powder, fly ash and silica fume, that is, M 矿粉 、M 粉煤灰 、M 硅灰 ;
[0089] Step 6: Determine the amount of water glass solution and the amount of sodium hydroxide according to the alkali-glue ratio N / B, the designed water glass modulus Ms and the initial water glass modulus Mo, that is, M 氢氧化钠 、M 水玻璃 ; The initial water glass modulus Mo refers to the modulus of the water glass raw material, which is an optional value. For example, the modulus of the water glass solution may be Mo=3.3, Mo=2.8, Mo=2.2, etc. The specific value is provided by the manufacturer. Generally, water glass with a lower modulus is selected, and Mo is between 2-3;
[0090] Step 7: Determine the amount of additional tap water to be added;
[0091] According to the water-binder ratio W / B and the water content in the water glass solution, determine the amount of additional tap water M to be added. 自来水 ; is the mass fraction of water in the water glass solution
[0092] Step 8: Determine the amount of aggregate;
[0093] According to the closest packing theory of particles, the ratio of 26-40 mesh, 40-70 mesh, and 70-110 mesh aggregates is determined as 26-40∶40-70∶70-110=x∶y∶z(α=0.23), where α is the distribution modulus. When α≥0.5, the concrete contains more coarse aggregates; when 0.2<α<0.5, the concrete contains more fine aggregates, and the particles of each component in the alkali-activated ultra-high performance concrete are smaller, so α=0.23;
[0094] Step 9: According to the sand-binder ratio and 26-40 mesh: 40-70 mesh: 70-110 mesh = x: y: z, determine the amount of three types of quartz sand: 26-40 mesh, 40-70 mesh, and 70-110 mesh, wherein the sand-binder ratio S / B = 1.0, which is a fixed value;
[0095] Step 10: Calculate the volume content and mass M of steel fiber according to the target compressive strength 钢纤维 ;
[0096] f c (X1, X2, X3, X4, 2 -110.81X2 2 -68.82X1X2)·(-0.79+9.24X3+18.88X4-17.62X3 2 -138.96X4 2 )·(1+0.17X5)
[0097] M 钢纤维 =7850kg / m3*X5;
[0098] Among them, X1 is the water glass modulus, X2 is the fly ash replacement rate, X3 is the water-binder ratio, X4 is the alkali-binder ratio, X5 is the steel fiber content, 5% is the silica fume replacement rate SF / B, 1.0 is the sand-binder ratio S / B, f c is the target compressive strength of concrete after incorporation of steel fibers;
[0099] Step 11: Conduct trial mix and evaluate whether the material properties of concrete meet the requirements. If so, end the mix design; if not, return to step 3 to adjust the mix parameters and the amount of each component.
[0100] Specific implementation method 2: Combination Figures 1 to 9This embodiment is described. Before determining the compressive strength and fluidity of the alkali-activated ultra-high performance concrete, the alkali-activated ultra-high performance concrete material is first determined. The alkali-activated ultra-high performance concrete material is composed of S95 mineral powder, F-type fly ash, silica ash, 26-40 mesh quartz sand, 40-70 mesh quartz sand, 70-110 mesh quartz sand, short straight steel fiber, flaky sodium hydroxide, water glass solution and water. This arrangement facilitates the preparation of ultra-high performance concrete. Other components and connection relationships are the same as those of the first specific embodiment.
[0101] Specific implementation method three: Combination Figure 1 To illustrate this embodiment, the curing system in step 2 of this embodiment is 90° steam curing for 48 hours. This arrangement can ensure that the alkali-activated ultra-high performance concrete quickly reaches the target strength and shortens the preparation cycle; and 90°C steam curing is also beneficial to reduce the cracking risk of the alkali-activated ultra-high performance concrete, compact the microstructure, and improve the durability of the concrete. The other components and connection relationships are the same as those of the specific embodiment one or two.
[0102] Specific implementation method four: Combination Figure 1 To illustrate this embodiment, the curing system of step 2 of this embodiment also includes a stirring system, including the following steps:
[0103] Step 1: Mix the mineral powder, fly ash and silica fume determined in step 5 and stir for 2 minutes;
[0104] Step 2: Add the quartz sand determined in step 9 and stir for 1 minute;
[0105] Step 3: Add the activator determined in step 6 and stir for 4 minutes;
[0106] Step 4: Add the steel fiber determined in step 10 and stir for 2-3 minutes. The test method is: the compressive strength test uses a 40×40×40mm3 cubic test block, and the test block loading system is 2.4kN / s±0.2kN / s.
[0107] Such an arrangement can ensure that there is no risk of fiber agglomeration during the concrete mixing process, and can ensure that the concrete components are fully mixed to obtain a more uniform alkali-activated ultra-high performance concrete. The other components and connection relationships are the same as any one of the specific implementation methods one to three.
[0108] Specific implementation method five: Combination Figure 1 This embodiment is described. The diameter of the short straight steel fiber in this embodiment is 0.2 mm and the length is 13 mm. This arrangement can ensure the basic static mechanical properties of alkali-activated ultra-high performance concrete and improve its impact resistance under dynamic load. The other components and connection relationships are the same as any one of the specific embodiments 1 to 4.
[0109] Specific implementation method six: Combination Figure 1 The total amount of cementitious material M in step 4 of this embodiment is described as follows: 总 =800-1100kg / m 3 .
[0110] Such a configuration is applicable to most ultra-high performance concrete. Other components and connection relationships are the same as any one of the specific implementation modes 1 to 5.
[0111] Specific implementation method seven: Combination Figure 1 To illustrate this embodiment, in step 52 of this embodiment, M 矿粉 、M 粉煤灰 、M 硅灰 The calculation formula is:
[0112] M 硅灰 =M 总 ×SF / B;
[0113] M 粉煤灰 =M 总 ×FA / B;
[0114] M 矿粉 =M 总 ×1-SF / B-FA / B.
[0115] Such arrangement facilitates accurate determination of the amount of each material. Other components and connection relationships are the same as any one of the specific implementation modes 1 to 7.
[0116] Specific implementation method eight: Combination Figure 1 In this embodiment, step six of the embodiment Such arrangement realizes accurate determination of material dosage by cooperating with related materials. Other components and connection relationships are the same as any one of the specific implementation modes 1 to 7.
[0117] Specific implementation method nine: Combination Figure 1 To illustrate this embodiment, the compressive strength of the alkali-activated ultra-high performance concrete to be prepared in step 1 of this embodiment is 100MPa-200MPa. The range of concrete suitable for preparation is relatively wide. The other components and connection relationships are the same as any one of the specific embodiments 1 to 8.
[0118] Combination Figures 1 to 17 Describe the embodiments of the present invention:
[0119] Step 1: Prepare alkali-activated ultra-high performance concrete with a compressive strength of 150 MPa and a fluidity of 260 mm;
[0120] Step 2: The plain concrete matrix strength is designed to be 110MPa;
[0121] Step 3: According to Figures 2 to 5 , select water glass modulus SiO2 / Na2O=1.1, fly ash replacement rate FA / B=10%, alkali-binder ratio Na2O / B=7%, water-binder ratio W / B=0.32, and silica fume replacement rate is fixed at SF / B=5%;
[0122] Step 4: Select the amount of adhesive material 800-1100kg / m 3 , take the total amount of rubber material M 胶总 =900kg / m 3 ;
[0123] Step 5: According to the total amount of adhesive material, the fly ash replacement rate FA / B and FA / B+SF / B+GBFS / B=1, SF / B=5% is a fixed value, and the amount of mineral powder, fly ash and silica fume is determined, that is, M 矿粉 、M 粉煤灰 、M 硅灰
[0124] M 硅灰 =M 胶总 ×SF / B=900kg / m3*5%=45kg / m 3
[0125] M 粉煤灰 =M 胶总 ×FA / B=900kg / m3*10%=90kg / m 3
[0126] M 矿粉 =M 胶总 ×(1-SF / B-FA / B)=900kg / m3*(1-5%-10%)=765kg / m 3
[0127] Step 6: Determine the amount of water glass solution and the amount of sodium hydroxide according to the alkali-to-glue ratio N / B, the designed water glass modulus Ms and the initial water glass modulus Mo, i.e., M 氢氧化钠 、M 水玻璃 ;
[0128]
[0129]
[0130] Step 7: Determine the amount of additional tap water M to be added based on the water-binder ratio (W / B), the amount of water glass solution and the mass fraction of water in the water glass solution. 水 ;
[0131]
[0132] Step 8: According to the closest packing theory of particles, the ratio of 26-40 mesh, 40-70 mesh, and 70-110 mesh aggregates is determined as 26-40:40-70:70-110=0.2536:0.2:0.5464 (α=0.23):
[0133] Step 9: According to the sand-binder ratio (sand-binder ratio S / B=1.0 is a fixed value) and 26-40 mesh: 40-70 mesh: 70-110 mesh = x: y: z, determine the amount of three types of quartz sand: 26-40 mesh, 40-70 mesh, and 70-110 mesh;
[0134] M 26-40目 =M 总 *S / B*x=900kg / m 3 *1.0*0.2546=228kg.m 3
[0135] M 40-70目 =M 总 *S / B*x=900kg / m 3 *1.0*0.2=180kg / m 3
[0136] M 70-110目 =M 总 *S / B*x=900kg / m 3 *1.0*0.5464=492kg / m 3
[0137] Step 10: Calculate the volume content and mass M of steel fiber according to the target compressive strength 钢纤维 ;
[0138] f c (X1, X2, X3, X4, 2 -110.81X2 2 -68.82X1X2)·(-0.79+9.24X3+18.88X4-17.62X3 2 -138.96X4 2 )·(1+0.17X5)
[0139] 150=(5.31+169.46*1.1+87.69*0.1-59.94*1.1^2-110.81*0.1^2-68.82*1.1*0.1 )*(-0.79+9.24*0.32+18.88*0.07-17.62*0.32^2-138.96*0.07^2)*(1+0.17*X5)
[0140] X5=1.49
[0141] M 钢纤维 =7850kg / m3*1m3*1.49%=117kg / m 3
[0142] Fluidity prediction formula:
[0143] f flow (X1,X2,X3,X4,X5,5%,1.0)=(-0.01+1.17X1+1.12X2-0.39X1 2 -0.172X2 2 )·(74.80-886.25X3+56055.50X4+625.00X3 2 -62499.99X4 2 +14700.00X3X4)·(1-0.02X5)
[0144] Among them, X1 is the water glass modulus, X2 is the fly ash replacement rate, X3 is the water-binder ratio, X4 is the alkali-binder ratio, X5 is the steel fiber content, 5% is the silica fume replacement rate SF / B, and 1.0 is S / B.
[0145] Step 11: Conduct trial mix and evaluate whether the material properties of concrete meet the requirements. If so, end the mix design; if not, return to step 3 to adjust the mix parameters and the amount of each component.
[0146] The complete configuration in this embodiment is shown in the following table:
[0147] Unit: kg / m 3
[0148]
[0149] Test results:
[0150] index Measured data Prediction data Relative error % Compressive strength(MPa) 157.7 150.0 4.89 Slump expansion (mm) 255 236 7.16
[0151] When the set requirements are met, the proportioning is completed.
[0152] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for designing the mix ratio of composite cementitious system alkali-activated ultra-high performance concrete, characterized in that: It includes the following steps: Step 1: Determine the compressive strength and fluidity of the alkali-activated ultra-high performance concrete to be prepared; Step 2: Determine the compressive strength and fluidity of plain concrete without steel fiber, as well as the curing system; Step 3: Select the fly ash replacement rate FA / B, the water glass solution design modulus Ms, Ms = n(SiO2) / n(Na2O), the alkali-binder ratio N / B and the water-binder ratio W / B; where n is the amount of substance, and the unit of n is mol; Step 4: Determine the total amount of cementitious material M 胶总 ; Step 5: Determine the amount of each component of the cementitious material; Select the fly ash replacement rate FA / B and the silica fume replacement rate SF / B as 5% as fixed values. According to FA / B+SF / B+GBFS / B=1, determine the amount of mineral powder, fly ash and silica fume, that is, M 矿粉 、M 粉煤灰 、M 硅灰 ; Step 6: Determine the amount of water glass solution and the amount of sodium hydroxide according to the alkali-to-glue ratio N / B, the design modulus Ms of the water glass solution and the initial modulus Mo of the water glass solution, i.e., M 水玻璃 、M 氢氧化钠 ; Step 7: Determine the amount of additional tap water to be added; According to the water-binder ratio W / B and the water content in the water glass solution, determine the amount of additional tap water M to be added. 自来水 ; is the mass fraction of water in the water glass solution; Step 8: Determine the amount of aggregate; According to the closest packing theory of particles, the ratio of 26-40 mesh, 40-70 mesh, and 70-110 mesh aggregates is determined as 26-40:40-70:70-110=x:y:z, α=0.23, α is the distribution modulus, when α≥0.5, the coarse aggregate is the majority in the concrete; when 0.2<α<0.5, the fine aggregate in the concrete is more, and the particles of each component in the alkali-activated ultra-high performance concrete are smaller, so α=0.23 is taken; Step 9: According to the sand-binder ratio and 26-40 mesh: 40-70 mesh: 70-110 mesh = x: y: z, determine the amount of three types of quartz sand: 26-40 mesh, 40-70 mesh, and 70-110 mesh, wherein the sand-binder ratio S / B = 1.0, which is a fixed value; Step 10: Calculate the volume content and mass M of steel fiber according to the target compressive strength 钢纤维 ; <h2 style=";text-align:left;direction:ltr">f<h2 style=";text-align:left;direction:ltr"> c <h2 style=";text-align:left;direction:ltr"> (X1,X2,X3,X4,X5,5%,1.0)=(5.31+169.46X1+87.69X2-59.94X1<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> -110.81X2<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> -68.82X1X2)·(-0.79+9.24X3+18.88X4-17.62X3<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> -138.96X4<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> )·(1+0.17X5) <h2 style=";text-align:left;direction:ltr">M<h2 style=";text-align:left;direction:ltr"> 钢纤维 <h2 style=";text-align:left;direction:ltr"> =7850kg / m3*X5; Among them, X1 is the design modulus of water glass solution, X2 is the fly ash replacement rate, X3 is the water-binder ratio, X4 is the alkali-binder ratio, X5 is the steel fiber content, which is expressed as volume fraction X5% vol., 5% is the silica fume replacement rate SF / B, 1.0 is the sand-binder ratio S / B, f c is the target compressive strength of concrete after incorporation of steel fibers; Step 11: Conduct trial mix and evaluate whether the material properties of concrete meet the requirements. If so, end the mix design; if not, return to step 3 to adjust the mix parameters and the amount of each component.
2. The method for designing the mix ratio of composite cementitious system alkali-activated ultra-high performance concrete according to claim 1, characterized in that: Before determining the compressive strength and fluidity of alkali-activated ultra-high performance concrete, the raw materials required for the preparation of alkali-activated ultra-high performance concrete are first determined. The alkali-activated ultra-high performance concrete materials are composed of S95 mineral powder, Class F fly ash, silica fume, 26-40 mesh quartz sand, 40-70 mesh quartz sand, 70-110 mesh quartz sand, short straight steel fiber, flaky sodium hydroxide, water glass solution and water.
3. The method for designing the mix ratio of composite cementitious system alkali-activated ultra-high performance concrete according to claim 2, characterized in that: The curing system in step 2 is 90° steam curing for 48 hours.
4. The method for designing the mix ratio of composite cementitious system alkali-activated ultra-high performance concrete according to claim 3, characterized in that: Step 2 also includes a stirring system, including the following steps: Step 1: Mix the mineral powder, fly ash and silica fume determined in step 5 and stir for 2 minutes; Step 2: Add the quartz sand determined in step 9 and stir for 1 minute; Step 3: Add the activator determined in step 6 and stir for 4 minutes; Step 4: Add the steel fiber determined in step 10 and stir for 2-3 minutes. The test method is: the compressive strength test uses a 40×40×40mm 3 Cubic test block, test block loading system is 2.4kN / s±0.2kN / s.
5. The method for designing mix proportions of composite cementitious system alkali-activated ultra-high performance concrete according to claim 2, characterized in that: The diameter of the short straight steel fiber is 0.2 mm and the length is 13 mm.
6. A method for designing mix proportions of composite cementitious system alkali-activated ultra-high performance concrete according to claim 4 or 5, characterized in that: The total amount of cementitious material used in step 4 is M 胶总 =800-1100kg / m 3 .
7. The method for designing mix proportions of composite cementitious system alkali-activated ultra-high performance concrete according to claim 6, characterized in that: Step 52, M 矿粉 、M 粉煤灰 、M 硅灰 The calculation formula is: M 硅灰 =M 胶总 ×SF / B; M 粉煤灰 =M 胶总 ×FA / B; M 矿粉 =M 胶总 ×1-SF / B-FA / B。 8. The method for designing mix proportions of composite cementitious system alkali-activated ultra-high performance concrete according to claim 7, characterized in that: Step 7 in is the mass fraction of SiO2 in the water glass solution; the mass of sodium hydroxide is calculated as follows: Available in, is the mass fraction of sodium oxide in the water glass solution.
9. A method for designing mix proportions of composite cementitious system alkali-activated ultra-high performance concrete according to claim 1 or 8, characterized in that: The compressive strength of the alkali-activated ultra-high performance concrete to be prepared in step 1 is 100MPa-200MPa.
Citation Information
Patent Citations
Alkali-activated and nano-enhanced early strength type ultra-high performance concrete and preparation method thereof
CN111848026A
Steel bar sleeve grouting material containing copper tailing sand and proportion setting method of steel bar sleeve grouting material
CN112299764A